A Phenomenological Study of Value (Moral) Education in a School of Kirtipur Municipality - Acharya, Milan (Educational Journal, 2023)
This study aims to explore how teachers experience on value education particularly related to moral education of students in a public school in Kirtipur. In addition, the study explores the challenges of maintaining value education that positively and adversely imparts quality education. A qualitative research design embedding phenomenological study was used in this study. Three secondary-level teachers were interviewed for more than half an hour each. The data were analyzed through thematic analysis. The finding shows students show a wide range of moral behaviors that make the importance of value education. In addition, Teachers face certain problems related to the curriculum, social environment, and family while transmitting values to students.